Dimorphism of [Bi2O2(OH)](NO3) – the ordered Pna21 structure at 100 K - Matthias Weil; Owen P. Missen; Stuart J. Mills (Acta Crystallographica Section E: Crystallographic Communications, 2023)
The re-investigation of [Bi2O2(OH)](NO3), dioxidodibismuth(III) hydroxide nitrate, on the basis of single-crystal X-ray diffraction data revealed an apparent structural phase transition of a crystal structure determined previously (space group Cmc21 at 173 K) to a crystal structure with lower symmetry (space group Pna21 at 100 K). The Cmc21 → Pna21 group–subgroup relationship between the two crystal structures is klassengleiche with index 2. In contrast to the crystal structure in Cmc21 with orientational disorder of the nitrate anion, disorder does not occur in the Pna21 structure. Apart from the disorder of the nitrate anion, the general structural set-up in the two crystal structures is very similar: [Bi2O2]2+ layers extend parallel to (001) and alternate with layers of (OH)− anions above and (NO3)− anions below the cationic layer. Whereas the (OH)− anion shows strong bonds to the BiIII cations, the (NO3)− anion weakly binds to the BiIII cations of the cationic layer. A rather weak O—H...O hydrogen-bonding interaction between the (OH)− anion and the (NO3)− anion links adjacent sheets along [001].